Bormasa MANAJEMEN PENGELOLAAN DANA DESA DALAM MENGATASI DAMPAK COVID’19 PADA DESA WUNLAH KECAMATAN WUARLABOBAR KABUPATEN KEPULAUAN TANIMBAR - Monica Feronica Bormasa; Yulius Luturmas (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
In order to adapt to the impact of Covid'19 (Corona Virus), the village government must be able to take village fund budget management policies by paying attention to the conditions and needs of the people in the village, this is done so that the solutions to the problems faced can be handled easily From the results of the research, the community felt that the most visible impact of covid'19 was the economic, health and social impacts, these three impacts made the community feel stressed because the sensitivity of the village government in overcoming these impacts was still far from what was expected. In this research, the method used is qualitative research method with qualitative descriptive research type. Based on the results of the research, the village government basically has to be wise in the management process of managing the Village Fund in taking urgent action against the impact of Covid'19 on the community, because it is slow in taking policies to help the community from the economic impact, and health which is an impact that affects people's lives. This happened because basically the policy in taking action was not overcoming the impact of covid', but the policy taken from the beginning of the emergence of covid'19 was to open a guard post and create a village entrance portal for outsiders who wanted to visit the village of Wunlah. This is a wrong policy.